Improving Learning Outcomes on the Material of Asmaul Husna through the Problem-Based Learning Model - Maryanto, Dedi (Department of Teacher Professional Education, Tarbiya and Teacher Training Faculty, UIN Sunan Gunung Djati Bandung, 2025)
This study aims to improve student learning outcomes in Islamic Education—specifically in the topic Asmaul Husna—through the implementation of the Problem-Based Learning (PBL) model. The research was motivated by low achievement and limited engagement resulting from conventional teaching methods such as rote memorization and lecturing. Using a mixed-method Classroom Action Research (CAR) design, the study was conducted in two cycles involving planning, acting, observing, and reflecting. The research subjects were fourth-grade students of SDN 005 Batubi Jaya, Natuna Regency. Data were collected using observation, documentation, and tests, then analyzed both qualitatively and quantitatively. The results show a steady improvement in student achievement: average scores increased from 57% in the pre-cycle to 70% in Cycle I and 76% in Cycle II, while mastery learning rose from 57% to 76%. Moreover, students demonstrated higher motivation, cooperation, and understanding of the moral significance of Asmaul Husna. The findings suggest that the PBL model provides an effective framework for integrating cognitive mastery with affective and spiritual growth, transforming Islamic Education into a more participatory, reflective, and meaningful learning experience.